Four decades of the Graf method in screening for developmental dysplasia of the hip (part I): Rightly the gold standard or of dubious benefit? - Ossendorff, Robert; Placzek, Sonja; Bornemann, Rahel; Walter, Sebastian G. (Frontiers in Pediatrics, 2022)
Introduction The method of infant hip sonography according to Graf is used for general hip screening in Serbia, Austria and Germany and is considered the gold standard. In other countries, such as the USA, however, it is not well accepted and claimed to lead to high costs and overtreatment. Aim of this study was to investigate in a recent review article how many of the mentioned sources contained sonograms that met the quality criteria as taught in Graf's ultrasound courses. Methods: A systematic review published by Sakkers et al. was analyzed in term of addressing quality criteria of Graf´s method. Studies that were suitable by title, abstract, manuscript, that contained an image of sonographic hip examination and that were accessible were included into analysis. Results Within the described review, there were 22 papers on the Graf method. 10 of these contained hip sonograms and were applicable for final analysis. Quality criteria according to Graf were not fulfilled within 5 out of these 10 papers. Within these papers there are examples of schematic sonograms that do not correspond with the quality criteria either. Conclusion Skepticism regarding the Graf method may be based on user errors and insufficient application of the Graf quality assessment algorithm, which results in high intra- and interobserver variations. Based on these findings, a working group was initiated to evaluate further work according to the same procedure (currently approx. 130 papers).